2018
DOI: 10.1038/s41588-018-0078-z
|View full text |Cite|
|
Sign up to set email alerts
|

The long tail of oncogenic drivers in prostate cancer

Abstract: Comprehensive genomic characterization of prostate cancer has identified recurrent alterations in androgen signaling, DNA repair, and PI3K among others. However, larger and uniform genomic analysis may reveal additional recurrently mutated genes at lower frequencies. Here we aggregate and uniformly analyze exome sequencing data from 1013 prostate cancers. We identify and validate a new class of E26 transformation-specific (ETS) fusion negative tumors defined by mutations in epigenetic regulators, as well as al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
744
6
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 696 publications
(794 citation statements)
references
References 41 publications
39
744
6
5
Order By: Relevance
“…The frequency of genomic copy number alterations in our mCRPC tumors was consistent with previous exome sequencing reports (Armenia et al, 2018; Beltran et al, 2013; Grasso et al, 2012; Robinson et al, 2015) (Figure 1A, Figure S2A). The percent of the genome altered in each sample ranged between 7% and 47% (median 23%; Table S1).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The frequency of genomic copy number alterations in our mCRPC tumors was consistent with previous exome sequencing reports (Armenia et al, 2018; Beltran et al, 2013; Grasso et al, 2012; Robinson et al, 2015) (Figure 1A, Figure S2A). The percent of the genome altered in each sample ranged between 7% and 47% (median 23%; Table S1).…”
Section: Resultssupporting
confidence: 92%
“…In contrast to previously published large-scale analyses of primary and metastatic prostate cancer that have largely focused on the coding genome (Abeshouse et al, 2015; Armenia et al, 2018; Barbieri et al, 2012; Beltran et al, 2013; Fraser et al, 2017; Robinson et al, 2015; Taylor et al, 2010; Wedge et al, 2018), we have performed whole genome analysis of metastases from 101 mCRPC patients at 109x depth of coverage in tumor samples. This coverage, two-fold deeper than previous efforts in this space (Wedge et al, 2018), and performed on a large patient cohort, has produced a unique resource for dissecting structural variation in metastatic prostate cancer samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was further strengthened by a recent TCGA study (4), wherein a subset of PCa patients' harboring SPOPmutation/CHD1-deletion exhibits elevated DNA methylation levels accompanied with frequent events of SPINK1 overexpression. Recently, a new subtype of ETS-fusion-negative tumors has been defined by frequent mutations in the epigenetic regulators and chromatin remodelers (55). Yet another study, using genome-wide methylated DNAimmunoprecipitation sequencing revealed higher number of methylation events in TMPRSS2-ERG fusion-negative as compared to normal and TMPRSS2-ERG fusion-positive PCa specimens (14), thus collectively, these independent findings reaffirm the critical role of epigenetic pathways engaged in the pathogenesis of SPINK1+ subtype.…”
Section: Discussionsupporting
confidence: 65%
“…The majority of SPOP mutations (~96%) detected thus far are missense heterozygous mutations that are located in the MATH domain (Cancer Genome Atlas Research Network, ; Armenia et al , ), a motif responsible for substrate recognition and interaction (Zhuang et al , ; Fig C). Similar to the findings reported previously (Zhang et al , ), SPOP hotspot mutation F133V almost completely abolished SPOP interaction with BRD4 (Fig A).…”
Section: Resultsmentioning
confidence: 99%